Sistema Opto-Electrónico de Comunicación Interactiva para Discapacitados - Minor, A.; Almazan, S.; González, A.; Leija, L.; Suaste, E. (Revista Mexicana de Ingenieria Biomedica, 1998)
The loss in ability of movement due to neuro-motor problems and other causes, have created the necessity of special interactive interfaces. Such interfaces, using the remaining mobility of the disabled, can give them an improved quality of life. Today, in Mexico, there are more 309 000 persons with neuro-motor problems that could be integrated to a dynamic life with one of these interactive interfaces, helping them obtain increased self-reliance and Independence. An opto-electronic interactive system for the disabled is presented. This Interactive System for the Disabled is a tool for disabled individuals that retain the ability of voluntary movement of head an eyes. The System replaces a conventional computer mouse. The whole system consists of a pair of conventional eyeglasses, in which we arranged two LED’s, one infra-red photodetector and one panel with four photodetectors over a PC’s monitor. The System allows movement across the screen through voluntary blinking (left button control). Healthy individuals successfully tested the System, performing various mouse operations on a PC. The results of the trials demonstrated this System provides efficient man-machine communication, using commercial or specific software. Performance trials were made under MS-DOS and WINDOWS.